1994
DOI: 10.1161/01.str.25.3.663
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection with a calpain inhibitor in a model of focal cerebral ischemia.

Abstract: Background and Purpose Excessive elevation of intracellular calcium and uncontrolled activation of calcium-sensitive events are believed to play a central role in ischemic neuronal damage. Calcium-activated proteolysis by calpain is a candidate to participate in this form of pathology because it is activated under ischemic conditions and its activation results in the degradation of crucial cytoskeletal and regulatory proteins. The present studies examined the effects of a cellpenetrating inhibitor of calpain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(89 citation statements)
references
References 45 publications
2
85
1
1
Order By: Relevance
“…Previous results demonstrating a requirement for Ca 2 þ (Figure 3c) and reports showing calpain as a major effector in excitotoxicity and ischemia [35][36][37] suggested that activation of this protease might be responsible for the NR2A cleavage induced by NMDA, as shown before for NR2B. 19 We first confirmed the activation of calpain in the in vitro model of excitotoxicity used in these experiments.…”
Section: Specific Decrease Of Nr2a Nr2b and Psd-95 In Focal Cerebralsupporting
confidence: 81%
See 3 more Smart Citations
“…Previous results demonstrating a requirement for Ca 2 þ (Figure 3c) and reports showing calpain as a major effector in excitotoxicity and ischemia [35][36][37] suggested that activation of this protease might be responsible for the NR2A cleavage induced by NMDA, as shown before for NR2B. 19 We first confirmed the activation of calpain in the in vitro model of excitotoxicity used in these experiments.…”
Section: Specific Decrease Of Nr2a Nr2b and Psd-95 In Focal Cerebralsupporting
confidence: 81%
“…Considering that calpain is activated very early during the ischemic process 36,37 and the results previously obtained in the in vitro model of excitotoxicity, it is very likely that this protease is responsible for the proteolytic processing of the NR2A and NR2B subunits occurring in ischemia. We confirmed calpain activation by the production of brain spectrin BDPs, paying special attention to the kinetics of the process (Figure 6b).…”
Section: Nr2a Subunit and Psd-95 Are Both Calpain Substrates In Cortimentioning
confidence: 90%
See 2 more Smart Citations
“…Calpain inhibitors have been reported to improve posthypoxic synaptic recovery in both neocortical (Hiramatsu et al, 1993) and hippocampal (Arling haus et al, 199 1) slices and to protect neurons both in the context of cytotoxic hypoxia in vitro and fol lowing transient global ischemia in vivo (Rami and Krieglstein, 1993). In recent studies, cell-pene trating calpain inhibitors have been reported to re duce the volume of infarction and to attenuate the increase in SBPs in models of focal ischemia (Bar tus et al, 1994;Hong et al, 1994). These results suggest that calcium-activated proteolysis is close ly involved in the process of ischemic neuronal damage and may offer a crucial target for achiev ing pharmacological neuroprotection in ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%